2014
DOI: 10.17796/jcpd.39.1.t44j06u21764j888
|View full text |Cite
|
Sign up to set email alerts
|

Microabrasion: A Treatment Option For White Spots

Abstract: The aim of the present study was to describe a clinical protocol for the treatment of white spots with the use of an abrasive material. A four-year-old patient presented with a white spot on tooth 51 and a white spot associated with a carious lesion in the cervical region of tooth 52. Treatment was planned with microabrasion and restoration of the upper right lateral incisor. Prophylaxis was first performed, followed by protection with a dental dam and the application of the abrasive material (silicon carbide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
3
0
2
Order By: Relevance
“…13 Clinical studies have confirmed the benefit of using microabrasion to obtain a good esthetic outcome for WSLs. 14,15 The components of microabrasion include 6.6% hydrochloric acid and 20to 160-lm-sized silicon carbide microparticles that removes superficial parts of a lesion by chemical erosion and mechanical abrasion. 16 One case report comparing the esthetic effect of resin infiltration and microabrasion for WSLs showed that the resin infiltration technique seemed more efficient, with a diminution of lesion size.…”
Section: Introductionmentioning
confidence: 99%
“…13 Clinical studies have confirmed the benefit of using microabrasion to obtain a good esthetic outcome for WSLs. 14,15 The components of microabrasion include 6.6% hydrochloric acid and 20to 160-lm-sized silicon carbide microparticles that removes superficial parts of a lesion by chemical erosion and mechanical abrasion. 16 One case report comparing the esthetic effect of resin infiltration and microabrasion for WSLs showed that the resin infiltration technique seemed more efficient, with a diminution of lesion size.…”
Section: Introductionmentioning
confidence: 99%
“…A duração e a quantidade das aplicações, por sessão, ainda não foram completamente estabelecidas na literatura 1,12,22,[30][31][32] . Alguns estudos preconizaram a execução de dez aplicações com duração de 10s cada 13,19 .…”
Section: Resultsunclassified
“…Os espécimes foram analisados quanto à perda de estrutura de esmalte utilizando-se análise gravimétrica 22 . Trata-se de avaliação indireta da eficiência de abrasão dos produtos testados, determinando-se a perda de massa do esmalte, em gramas (g).…”
Section: Análise Gravimétricaunclassified
“…When necessary, the microabrasion technique may be combined with other treatment approaches in order to improve the final esthetic result. Treatments such as dental bleaching may be useful to whiten the yellowish part of the tooth when there is a great enamel reduction and reduce contrast with the rest of the surface [6,10,18,21]. If, afterwards, there is still a need to further improve results, a resin-infiltration technique may be attempted and later, if necessary, a direct composite restoration.…”
Section: Discussionmentioning
confidence: 99%